Aktualisasi Sila Persatuan Indonesia dalam Semangat Gotong Royong Bangsa - Maria Hermina Bhebhe; Aprilia W. Bhoko Fao; Yohana Elma Sarina Ito Wea; Maria Fransiska Manggus; Sisilia Sela; Maria Eleonora Lejo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research aims to examine and analyze the actualization of the third principle of Pancasila, namely